Representations of Hybridity in Aquaman (2018): A Postcolonial Reading - Anggun Aida Sholiha; Azzahra Dwi Rizky Faradilla; Fatimah Nilam Sari; Intan Rahma Sari; Nailah Hanan Fathiyah Salma; Umi Hani (EUFONI: Journal of Language, Literary, and Cultural Studies, 2025)
This study examines the representation of hybridity in the film Aquaman (2018), directed by James Wan, through the lens of Homi K. Bhabha’s postcolonial theory. While existing studies on Aquaman predominantly focus on mythological themes, heroism, or visual spectacle, limited attention has been given to its portrayal of postcolonial identity formation and hybridity. The purpose of this research is to analyze how hybridity is constructed through the main character, Arthur Curry, whose identity emerges from his dual belonging to the human world and the Atlantean realm. Employing a qualitative descriptive method, this study analyzes key scenes, narrative moments, and character dialogues that explicitly depict Arthur Curry’s negotiation of identity between two cultural worlds. The findings reveal that hybridity functions as the central mode of identity formation in Arthur Curry’s character. His identity is articulated through an in-between position marked by cultural ambivalence and an unstable sense of belonging. The interaction between the surface world and Atlantis further operates as a third space that enables the negotiation of meaning and challenges rigid binary oppositions. Moreover, Arthur’s character development demonstrates identity as a dynamic process of becoming, in which hybridity is continuously shaped and redefined rather than fixed. Overall, this study concludes that Aquaman (2018) can be understood as a postcolonial cultural text that represents hybridity as a fluid and ongoing process of identity formation within popular cinema.